Knowledge of mothers regarding infant’s developmental milestones in four domains (gross motor, fine motor, language and personal and social) – A cross sectional study - Pooja Thakur; Nalina Gupta (Journal of Family Medicine and Primary Care)
Background: In India, children with neurodevelopmental disabilities are being referred late. One of the possible reasons could be lack of mothers’ knowledge regarding developmental milestones. Hence, the objective of this study was to assess the knowledge of mothers regarding infants’ developmental milestones in four domains using a self-drafted questionnaire and to enlist the factors influencing mothers’ knowledge if any. Methods: This was an observational study. The study was conducted using a questionnaire which was drafted, face-validated, and pilot-tested. The final drafted questionnaire was used for the data collection. The duration for data collection was June 2019 to November 2019; data were collected from Dhiraj General Hospital. Inclusion criteria of the study were mothers in the age range of 18–40 years and those who were willing to participate in the study. A total of 100 mothers were interviewed on one-to-one interview basis. Collected data were entered in Excel sheets and were analyzed using descriptive analysis. Results: 73% mothers were aware regarding head holding in the gross motor domain, 61% mothers were aware regarding hand to mouth in the fine motor domain, 41% mothers were aware regarding bisyllables in the language domain, and 64% mothers were aware regarding when an infant starts waving bye-bye in the personal social domain. Conclusions: Mothers were more aware about the gross motor and personal-social milestones as compared to that of language and fine motor milestones. Our results cannot be generalized.